Reception Analysis of the Bullying Issue in the Korean Drama Series Boyhood - Latif Ahmad Fauzan; Bilbina Alifia Maghfiruha (Lavish Opulent Education, 2025)
This study aims to understand how audiences perceive bullying scenes depicted in the Korean drama series Boyhood. The drama portrays various forms of bullying experienced by the main character, Jang Byeong Tae, which reflect social phenomena that also occur in Indonesia. This research employs a qualitative approach using reception analysis based on Stuart Hall’s encoding/decoding theory. Data were collected through in-depth interviews with nine informants who had watched the entire series. The findings reveal that audience reception falls into three categories: dominant-hegemonic, negotiated, and oppositional readings. Most informants expressed empathy toward the bullying victim and regarded the drama as a reflective medium to raise awareness about bullying issues. However, some informants felt that the physical violence scenes were exaggerated and less relevant to the Indonesian context. This research is expected to serve as a reference for media scholars and content creators in presenting social issues more responsibly.